Acetic acid fermentation of kuini (Mangifera odorata) and its potential substrate for human health - Hazniza Adnan,; Mohd Shukri Mat Ali,; Hadijah Hassan,; Mohd Norfaizal Ghazalli,; Zul Helmey Mohamad Sabdin,; Musaalbakri Abdul Manan,; Nur Syafiqah Nadhra Ramli, (Penerbit Universiti Kebangsaan Malaysia, 2019)
The kuini (Mangifera odorata) fruit has a strong scent, attractive orange-yellow colour of flesh and sweet-sour taste. Since ages, kuini parts have been used in folk medicine such as fever indicated that kuini contains prophylactic measures against certain illness and rich of beneficial constituents such as phenolics. In this study kuini underwent fermentation using inoculum (GAB) containing acetic acid bacteria of Gluconacetobacter sp. and the changes during fermentation were then observed. The objectives were (1) to identify the potential of kuini flesh as substrate to GAB inoculum, and (2) to evaluate the physicochemical and nutritional changes during fermentation process. Fermentation of kuini flesh had changed the acidity and affects the growth of inoculum and its biocellulose yield. Results indicated that fermentation using 3% of kuini substrate (KF3) exhibited slightly lower pH compared to 5% of kuini substrate (KF5) while the acetic acid production in KF3 was found higher than KF5. This finding indicated that only small amount of kuini at 3% (w/v) of substrate was able to change the physicochemical property in kuini fermentation thus create a favourable environment for the growth of GAB inoculum and production of its biocellulose. Effect of sucrose in the fermentation also showed that acidity and growth of inoculum were increased with increase of sucrose concentration however depressed the yield of biocellulose. Sucrose at 5 to 20% (w/v) in kuini fermentation had given no distinct effect on the pH and acetic acid content. During fermentation the GAB inoculum had exhibited a poor growth in control, a high growth at 5% (w/v) sucrose and moderate growth between 10-20 % (w/v) sucrose in kuini substrates. The control and kuini substrate at 5% (w/v) sucrose also exhibited a high production of biocellulose (13.7 %) whereas high sucrose content in kuini substrate had exhibited low production of biocellulose (5.1%). The increase in sucrose concentration was found concurrently enhanced the total phenolic content and antioxidant activity during the fermentation. High total phenolic content (200 mg/mL GAE) was obtained from 15-20% (w/v) sucrose with control exhibited the least with less than 100 mg/mL GAE. All samples had exhibited high antioxidant activity at which the addition of sucrose into kuini substrate had increased nearly double the antioxidant activity. In conclusion, acetic acid fermentation able to change the physicochemical and nutritional properties of kuini flesh into a health beneficial fermented kuini produced with high antioxidant activity. The fermented kuini produce also contains prophylactic property and therefore potential to be studied for human health application. In near future the antimicrobial activity of kuini substrate with bioactive property against certain bacteria causing health-illness is also interested to be studied.